Optimización de las operaciones en la empresa textil Jori Bordados mediante la aplicación de gestión de procesos - Chantera Donoso, Jessica Amanda (2019)
Jori embroidery is an organization that make clothing that is marketed in Quito, also it has some services such as embroidery, clothing, sublimated and Vinyl, it is in the Tejar neighborhood in Quito downtown. This degree work represents a proposal for improvement based on the process management methodology and manufacturing tools in the Jori embroidery organization...